Wissenschaft Weltoffen 2017 Daten und Fakten zur Internationalität von Studium und Forschung in Deutschland - DAAD, Referat Forschung und Studien (W. Bertelsmann Verlag, 2017)
The Baltic Sea Region is an important example of the regionalisation of international academic cooperation. This is the conclusion of the 17th DAAD study on international scientific mobility. On an annual basis, the paper documents the status quo as well as developments in the internationality of German science and universities. The study also examines other countries such as the USA, China, and Great Britain. The emphasis of this issue lies on academic mobility and cooperation within the Baltic Sea Region. Among other sources, the included mobility analyses by scientists, students, and doctoral students are based on international data by the OECD and UNESCO as well as on national data by the German Federal Statistical Office. In combination with other indicators, this data offers a valid foundation for long-term analyses. "Cosmopolitan Academia" (Wissenschaft Weltoffen) is published as a bilingual German/English issue. The study text and diagrams are available for free download at wbv